Development and Validation of Infrared Spectroscopy Methods for Rutin Compound Analysis - Auha, Nydia Ashfi; Alauhdin, Mohammad (Universitas Negeri Semarang, 2021)
Rutin is a glycoside resulting from the condensation of the aglycone quercetin with the sugar rutinose. Some study show that rutin can reduce cardiac hypertrophy and improve heart health. Appropiate levels can optimize rutin performance, it is necessary to develop methods for rutin assays and their validation. This study aims to develop an analytical method for rutin compound with FTIR and their validity. The FTIR methods has several advantages including simple preparation, fast scanning, high resolution, does not take long, and without the use of hazardous reagents and can be used for qualitative and quantitative analysis at the same time. The standard rutin with mass variation (0.5-1.75 mg) was mixed homogeneously with KBr so that the total mass was 16 mg. The mixture of rutin and KBr then made into pellets with a hydraulic machine so that transparent pellets were obtained. Measurement were carried out at wave number 4000-400 cm-1 with 8 scanning. Methods validation include linearity, LoD, LoQ, and precision test. Based on the result of the analysis, the typical peak of rutin compounds is in the wave number range of 900-690 cm-1 namely aromatic C-H. Rutin had linearity, LoD, and LoQ of 0.8719, 0.7 mg, and 2.5 mg, and %RSD repeatability 17.68 % and %RSD reproducibility 17.62 %.